Bar Examination: A Verb, Not A Noun - Marsha Griggs (Washington University Journal of Law and Policy, 2025)
The legal profession, long steeped in tradition, is witnessing a transformative shift in the protocols for licensing new attorneys. Multiple jurisdictions are moving away from reliance on standardized testing as the sole gateway to law practice and are developing individualized (and potentially reciprocal) systems of state licensure. Ironically, the planned launch of a new standardized exam—the NextGen bar exam—appears to be a major catalyst in the transformation of state licensure pathways. This shift has the potential to realign the regulatory hierarchy in attorney admission. Such a realignment is vital to the preservation of lawyer self-governance, and it offers great promise for a more client-centered focus in legal education. This Article examines the many new developments in attorney licensure taking place in the United States and offers an account of their advantages and limitations, including their potential for multijurisdictional practice. By deconstructing the varied new or improved ways to license new attorneys, this Article will aid state supreme courts and state examining boards that wish to explore exam alternatives. The summary processes and recommendations described offer guidance on the array of licensing measures that are available and the mechanics of their implementation. This Article also pushes back against the normative and reductionist theory of bar examination. It applies a new legal realism lens through which to view the construct of bar examination. In so doing, it offers a multimodal roadmap to a co-regulated profession that is free of unnecessarily restrictive barriers to entry. This Article presents information that will aid law students aspiring to become licensed attorneys in determining where and through which modality to pursue licensure. This Article continues an important national conversation about attorney self-regulation and offers new avenues to engage members of the legal profession in their own governance.
Keywords: Attorney Licensure Reform; Bar Exam Alternatives; Legal Education Innovation